1977
DOI: 10.1346/ccmn.1977.0250204
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Spectra of Dioctahedral Smectites

Abstract: Abstrac~M6ssbauer spectra of 15 smectites were investigated. In these samples, ferric iron occupies both M(1) and M(2) octahedral sites, the distribution being partly determined by the relative covalency of the bonds formed.The quadrupole splittings are linearly related to b -3. They show that Fe 3+ octahedra are much more distorted in montmorillonite and beidellite than in nontronite and volkonskoite and that M(I) sites are more prone to change than M(2). Ferrous iron occurs in relatively undistorted octahedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 16 publications
4
30
1
Order By: Relevance
“…The M6ssbauer spectrum was resolved into two Fe 3+ doublets, with relative intensities of -1:2, indicating that the Fe content of all octahedral sites is equivalent, as previously discussed (Rozenson and Heller-Kallai, 1977). The spectrum remained unchanged for samples heated to 350~ at which temperature the Q.S.…”
Section: Nontronite (Table 2 Figures 2 and 8)supporting
confidence: 67%
See 2 more Smart Citations
“…The M6ssbauer spectrum was resolved into two Fe 3+ doublets, with relative intensities of -1:2, indicating that the Fe content of all octahedral sites is equivalent, as previously discussed (Rozenson and Heller-Kallai, 1977). The spectrum remained unchanged for samples heated to 350~ at which temperature the Q.S.…”
Section: Nontronite (Table 2 Figures 2 and 8)supporting
confidence: 67%
“…If a larger Q.S. of Fe 3+ doublets indicates greater site distortion, as is generally accepted (Bancroft, 1974), it may be concluded that sites occupied by Fe 3+ in iron-poor minerals are more distorted after dehydroxylation than those in their iron-rich counterparts, as was previously observed for the original minerals (Rozenson and Heller-Kallai, 1977).…”
Section: Clays and Clay Mineralsmentioning
confidence: 57%
See 1 more Smart Citation
“…However, Fe" could not have been retained in this oxidation state unless incorporated in octahedral clay layers such as illite, smectite or vermiculite (cf. CARROLL, 1958, ROZENSON andHELLER-KELLAI, 1977). The observed Fe 31 species can be attributed to goethite.…”
Section: Mossbauer Spectroscopymentioning
confidence: 93%
“…The presence of clay minerals was established by X-ray diffraction studies (Table 2). These two doublets can therefore also be attributed to Fe" ions that are incorporated in the octahedral smectite layers (GOODMAN et al, 1976;ROZENSON and HELLER-KELLAI, 1977). On the basis of Mossbauer data alone, it is im possible to select one of these assignments.…”
Section: Mossbauer Spectroscopymentioning
confidence: 99%